Case Analysis Of Wal-Mart Stores In China - Yao, Shu Ping (2005)
Wal-Mart, the world's largest retailer entered into China market in 1996. To improve its current situation, in this research we do PEST, SWOT analysis and develop mission and vision for Wal-Mart and give suggestions and develop strategies for Wal-Mart's future development in China market.